PENGARUH PENGETAHUAN, KEPERCAYAAN DAN KESADARAN UNTUK BERZAKAT TERHADAP KEPUTUSAN MEMBAYAR ZAKAT PROFESI DI BAZNAS KOTA JAMBI - Mustajiba (EKSYA : Jurnal Ekonomi Syariah, 2024)
This research is based on a framework of thinking about the influence of trust on the decision to pay zakat at BAZNAS Jambi City. The problem is that few people distribute zakat through BAZNAS, the collection of zakat funds received is not appropriate compared to the regional potential and the number of Muslim residents in Jambi City. This research aims to find out whether trust influences the decision to pay zakat, as well as how to increase public trust in BAZNAS Jambi City. This research uses quantitative methods with a sample size of 100 muzakki with a sampling technique using the Solvin Formula. Data collection using questionnaires, interviews and documentation methods. Meanwhile, the data analysis technique is carried out using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) or shortened to SEM – PLS. Each hypothesis will be analyzed using the Smart PLS version 2.0 application to test the relationship between variables. The research results obtained an estimated coefficient value of 0.057 with a probability value of 0.695 > 0.1. This means that knowledge has a positive but not significant effect on knowledge of issuing zakat. The results of this research are the same as the results of research conducted by Satrio & Siswanto (2016). However, this research shows that increasing knowledge from professional results does not have a significant impact on people's knowledge in paying professional zakat. This is caused by the pressure on professional results in the people of Jambi city. Where, the amount of knowledge received by farmers is dynamic depending on the income cycle of the community's profession.